Neurotoxicity and hyperphosphorylation of tau protein induced by the amyloid peptide oligomers involve different glutamate dependent and independent mechanisms: Nonhuman/Target identification and validation studies: Amyloid. (7th December 2020) - Henriques, Alexandre; Rouvière, Laura; Farrugia, Clémence; Poindron, Philippe; Callizot, Noelle
Abstract: Background: Alzheimer's disease is characterized by the extracellular accumulation of senile plaques composed of amyloid beta and the intracellular deposition of neurofibrillary tangles composed of hyperphosphorylated tau (Tp). Aβ oligomers (AβO) induced sequential damages starting with synapses loss, followed by the neurite network disorganization and finally the neuronal death. In this study, we deeply investigated the role of glutamate and its receptors (mGluR5 and NMDARs) in the AβO neurotoxicity and in the Tp. Method: Using primary cultures of rat embryonic cortical neurons, the AβO toxicity was investigated in presence or absence of glutamate receptor antagonists (MPEP, Ifenprodil, MK801, memantine...). The AβO effects on the glutamate release and on the Ca 2+ flux were studied in presence or absence of BAPTA in the medium. In addition, the AβO effect on the hyperphosphorylation of Tau was studied. Different sites of hyperphosphorylation were investigated (AT100, AT8 and Thr231 involving the DAPK1 and GSK3β). Result: We showed that 5 min after AβO application, a large release of glutamate was seen in the extracellular medium. This release was immediately followed by a Ca 2+ entrance in the neurons. In absence of extracellular Ca 2+, the caspase‐3 activation was abolished as well as the neuronal death. Similarly, in presence of NMDAR or mGluR5 antagonists, the neuronal death was abolished, by contrast, Tau hyperphosphorylation and aggregation was still observed. Conclusion: Altogether, these findings showed the crucial role of glutamate and Ca 2+ in the AβO acute neuronal death, and demonstrated that the effects on Tp might not involve the NMDAR and the mGluR5.